Actinopterygii, Characiformes, Characidae: Ectrepopterus uruguayensis (Fowler, 1943): New record for Argentina - Miquelarena, Amalia Maria (2013)
Ectrepopterus uruguayensis Fowler was recently redescribed, with occurrence in lower tributaries of Río de la Plata and lower Río Uruguay, Uruguay. Herein its occurrence is extended and confirmed to Argentina, arroyo El Molino, in Uruguay Department, Entre Ríos Province, Uruguay drainage.